Sustainability analysis of livestock projects focused on food and nutrition security: the MESMIS proposal - Linares Díaz, Alejandro José (2019)
The paper is based on the relationship between sustainability, development, and the direct implications on populations susceptible to problems related to food and nutritional insecurity. The article aimed to propose an assessment of the effect a livestock project could have to generate a favorable change in the living conditions of people who suffer from hunger, taking into account the unique conditions of each population and actions that do not threaten the survival or sustainability of future generations. This topic should be studied using an appropriate methodology that addresses the impact in a temporal space by a cyclical analysis of productivity, stability, reliability, resilience, adaptability, equity, and self-dependence of projects. Therefore, the methodology recommended is the one considered most effective by the different authors.